REALISING THE RIGHT TO DEVELOPMENT IN GHANA THROUGH ITS PARLIAMENT (The Pretoria Student Law Review, 2023)
The right to development (RTD) remains a controversial subject at the international level due to disagreements over its nature as a collective and a people’s right. This notwithstanding, the RTD is recognised by the African human rights system as a collective right encompassing all fundamental rights and freedoms. Besides, the ratification of the African Charter on Human and Peoples’ Rights (ACHPR), which recognises the RTD coupled with the implicit recognition of the RTD in the 1992 Constitution of the Republic of Ghana, makes the RTD an entitlement for Ghanaians. However, its realisation by the state through the executive appears challenging, considering the level of development in Ghana. This article, therefore, explores an alternativefocused on legislative measures. The article seeks to demonstrate the extent to which the RTD can be realised in Ghana through its Parliament. It argues that removing the constitutional constraints on Parliament will potentially make the institution contribute significantly towards the realisation of the RTD.